Health care utilisation preceding relapse or second malignant neoplasm after childhood acute lymphoblastic leukaemia: a population-based matched cohort study - Alina Zalounina Falborg; Peter Vedsted; Kjeld Schmiegelow; Birgitte Klug Albertsen; Steen Rosthøj; Karen Schow Jensen; Henrik Schrøder; Michael Thude Callesen (BMJ Open)
Objectives To investigate health care utilisation including both primary and secondary health care 6 months before the diagnosis of a relapse or a second malignant neoplasm (SMN) in survivors of childhood acute lymphoblastic leukaemia (ALL).Design and setting A Danish population-based matched cohort study linking multiple nationwide registries.Participants Participants were recruited from a total of 622 childhood ALL 2.5-year event-free survivors diagnosed between 1994 and 2015. Cases were survivors developing a relapse or an SMN and references were survivors still in first remission. Each case was matched with five references on age, sex, treatment protocol and risk group.Primary outcome measures Consultations in general practice and hospital the last 6 months before relapse or SMN. Cases and references were compared with monthly incidence rate ratios (IRRs) from negative binomial regression models.Results Of the 622 childhood ALL survivors, 60 (9.6%) developed a relapse (49) or an SMN (11) and 295 matched references were identified. Health care utilisation in general practice increased among cases the last month before the event compared with references with an IRR of 2.71 (95% CI 1.71 to 4.28). Data showed a bimodal structure with a significantly increased number of visits 4, 5 and 6 months before the event. Hospital health care utilisation increased 2 months before the event in cases with an IRR of 5.01 (3.78 to 6.63) the last month before the event and an IRR of 1.94 (1.32 to 2.85) the second-last month comparing cases and references.Conclusions Survivors of childhood ALL developing a relapse or an SMN have a short period of increased health care utilisation before diagnosis. At hospital, this might be explained by pre-diagnostic examinations. In general practice, data suggest a bimodal structure with children later developing a relapse having more contacts also half a year before the relapse, suggesting that there could be early warnings.